Soft computing applications : proceedings of the 7th International Workshop Soft Computing Applications (SOFA 2016). Volume 1 /: proceedings of the 7th International Workshop Soft Computing Applications (SOFA 2016). Volume 1. ([2018]) - Unknown
No abstract available